Factors Associated with #MeToo Involvement Among College Students - Hoffman, Chrystina (American journal of criminal justice, 2021)
Sexual violence is a topic that has received increasing national attention and has been identified as a commonly occurring social issue. In response to the failure of the criminal justice system (and society at large) to adequately respond to the prevalence of sexual victimization, the #MeToo movement (which involves posting the #MeToo hashtag on social media) has acted as a mechanism to expose systemic oppression and abuses of power, while also holding perpetrators of sexual violence accountable for sexual abuse and harassment. There is growing popularity in utilizing the internet to raise awareness about social issues and to generate participation in collective action. While most research investigating factors associated with social movement participation has been primarily confined to collective identity as a precursor to in-person activism, less is known about other predictors (e.g., demographic characteristics) of social and, more specifically, digital activism. Using data collected from 626 undergraduate college students, the current study examines the impact of various demographic characteristics, collective identity, self-esteem, self-control, and attitudes towards sexual coercion on participation in the #MeToo movement in various forms (i.e., posting the #MeToo hashtag on personal social media accounts; signing a #MeToo petition; attending a #MeToo protest or rally). Results indicate that demographic characteristics, collective identity, Greek membership/collegiate athletics, and sexual violence programming are significantly associated with #MeToo involvement. Policy implications and recommendations for future research are discussed.